Use of Eucalyptus DNA profiling in a case of illegal logging. Issue 6 (November 2020) - Roman, Madeline G.; Gangitano, David; Figueroa, Alejandra; Solano, Jaime; Anabalón, Leonardo; Houston, Rachel
Highlights: Nine STR markers for Eucalyptus were evaluated for variability and profile quality. Dinucleotides were more variable but larger motifs provided better quality profiles. STRs were used to compare samples from a case study involving suspected wood theft. Abstract: Eucalyptus is grown world-wide for paper pulp, solid wood, and other industries. Theft or illegal cutting of the trees causes hardship to owners of plantations and countries whose economies rely on the sale and export of eucalyptus products. Unfortunately, many of these crimes go unpunished due to lack of forensic evidence. Over 1200 short tandem repeat (STR) markers have been identified in the genomes of genus Eucalyptus and related species. However, their importance and utility in aiding forensic investigations of wood theft have not been explored. This study evaluated nine STRs for diversity and applied them to a case involving suspected wood theft. As expected, three dinucleotide STR markers showed greater variability but resulted in harder to interpret profiles. Four STR tetranucleotide markers evaluated in this study were found to contain additional repeat structures (dinucleotide or trinucleotide) that enhanced their variability but resulted in profiles with peaks at multiple stutter positions and heterozygote peak imbalance. The most promising STR markers were EGM37 and EMBRA 1374. Though less variable, they yielded robust and reproducible DNA profiles. All nine STR markers were applied to a case involving suspected wood theft. Samples were collected from seized wood and from remaining stumps in a plantation. No DNA match was found, thus eliminating the evidence samples as having originated from the forest. Dendrochronology analysis also resulted in an exclusion. This case study represents the first report using STR markers in any eucalyptus species to provide DNA evidence in a case of suspected wood theft.